Comprehensive nutrient consumption estimation and metabolic profiling during ketogenic diet and relationship with myocardial glucose uptake on FDG-PET. (2nd April 2022) - Selvaraj, Senthil; Seidelmann, Sara B; Soni, Meshal; Bhattaru, Abhijit; Margulies, Kenneth B; Shah, Svati H; Dugyala, Supritha; Qian, Chenao; Pryma, Daniel A; Arany, Zolt; Kelly, Daniel P; Chirinos, Julio A; et al.
Abstract: Aims: The ketogenic diet (KD) is standard-of-care to achieve myocardial glucose suppression (MGS) for assessing inflammation using fluorine-18 fluorodeoxyglucose–positron emission tomography (FDG-PET). As KD protocols remain highly variable between centres (including estimation of nutrient intake by dietary logs for adequacy of dietary preparation), we aimed to assess the predictive utility of nutrient intake in achieving MGS. Methods and results: Nineteen healthy participants underwent short-term KD, with FDG-PET performed after 1 and 3 days of KD (goal carbohydrate intake <20 g/day). Nutrient consumption was estimated from dietary logs using nutrition research software. The area under receiver operating characteristics (AUROC) of macronutrients (carbohydrate, fat, and protein intake) for predicting MGS was analysed. The association between 133 nutrients and 4 biomarkers [beta-hydroxybutyrate (BHB), non-esterified fatty acids, insulin, and glucagon] with myocardial glucose uptake was assessed using mixed effects regression with false discovery rate (FDR) correction. Median (25th–75th percentile) age was 29 (25–34) years, 47% were women, and 42% were non-white. Median (25th–75th percentile) carbohydrate intake (g) was 18.7 (13.1-30.7), 16.9 (10.4-28.7), and 21.1 (16.6-29.0) on Days 1–3. No macronutrient intake (carbohydrate, fat, or protein) predicted MGS ( c -statistic 0.45, 0.53, 0.47, respectively). Of 133 nutrients and 4 biomarkers, only BHB was associated with myocardial glucose uptake after FDR correction (corrected P -value 0.003). Conclusions: During highly supervised, short-term KD, approximately half of patients meet strict carbohydrate goals. Yet, in healthy volunteers, dietary review does not provide reassurance for adequacy of myocardial preparation since no clear thresholds for carbohydrate or fat intake reliably predict MGS. Graphical Abstract: